Advancements in the interventional therapy and nursing care on deep vein thrombosis in the lower extremities - Jia, Chun-yi; Dai, Dan-dan; Bi, Xin-yuan; Zhang, Xia; Wang, Yi-ning (Frontiers in Medicine, 2024)
This review examines recent advancements in interventional treatments and nursing care for lower extremity deep vein thrombosis (DVT), highlighting significant innovations and their clinical applications. It discusses the transition to novel anticoagulants such as Direct Oral Anticoagulants, which offer a safer profile and simplified management compared to traditional therapies. Mechanical interventions, including balloon angioplasty and venous stenting, are detailed for their roles in improving immediate and long-term vascular function in acute DVT cases. Furthermore, the use of image-guided techniques is presented as essential for enhancing the accuracy and safety of DVT interventions. Additionally, this study outlines advances in nursing care strategies, emphasizing comprehensive preoperative and postoperative evaluations to optimize patient outcomes. These evaluations facilitate tailored treatment plans, crucial for managing the complex needs of DVT patients. Long-term care strategies are also discussed, with a focus on patient education to ensure adherence to treatment protocols and to prevent recurrence. The synthesis aims to inform healthcare professionals about cutting-edge practices in DVT management, promoting a deeper understanding of how these advancements can be integrated into clinical practice. It also underscores the necessity for ongoing research to address challenges such as cost-effectiveness and patient compliance, ensuring that future treatments are both accessible and effective.